Indonesian Adaptation of Academic Procrastination - Short Form (APS-S): Validity and Reliability - Abdullah Fathur Rasyid; Arjuna Putra Darma Wangsya; Dessi Aryanti Dwi Putri (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2023)
Academic procrastination is defined as the behavior of delaying assignments related to the academic context. Academic procrastination commonly occurs at various levels of education, especially with undergraduate students. Previous studies reported that undergraduate students who indulged in procrastination show poor academic performance and trigger a decrease in psychological functioning. The availability of good instruments can help portray this phenomenon, especially since there have been no reports regarding instruments that measure academic procrastination in Indonesia. The aim of this study was to examine the construct validity and reliability of Academic Procrastination Scale-Short Form (APS-S) in Indonesian context. 452 undergraduate students were recruited as participants of this study. The sampling technique used is a non-probability sampling technique. A Confirmatory Factor Analysis (CFA) and reliability analysis were performed to examine the structural validity and internal consistency of the instrument, respectively. Results indicated that all 5 items of APS-S were unidimensional and had satisfactory construct validity and internal consistency. Thus, The APS-S is valid and can be used by future researchers as a concise instrument for measuring academic procrastination in the Indonesian context.